The importance of value creation in smart city initiatives: An ecosystem approach - Ivette M. F. Oomens; Bert M. Sadowski (International Telecommunications Society (ITS), 2017)
Within the growing literature on smart cities, much research has focused on issues related to the formation stage and the roles of different actors in these initiatives. The large number of failures of smart city initiatives, however, points at an existing gap between the understanding of the formation of these initiatives and the practice of their management. In this context, the purpose of this paper is to address this research gap by discussing determinants of smart city initiatives and the experiences in smart city management. By taking an innovation ecosystem perspective, the paper focuses on the management experiences of four smart city initiatives (WoonConnect, Mobilty Portal, Vehicle2Grid, Straatkubus) in the Netherlands. The empirical research has been undertaken during the period May and June 2016. In linking to the discussion on smart cities, the research shows that most studies on smart cities have focused on the formation stage of the initiative and the roles of partners in these initiatives. In order to better understand problems surrounding smart city projects, it is necessary to examine the fundamental business model underlying these initiatives (i.e. processes of value creation and appropriation) and the role of business partners in these ventures. By using an innovation ecosystem perspective, the paper is able to identify shortcomings of existing approaches in smart city research related to the (static) form of analysis and the firm-level type of analysis. For smart city managers, key issues related to smart city projects are rooted in the second stage of managing these ventures (i.e. the coordination stage) and the role of private firms in this stage.
Keywords: 330